Isotope disequilibrium effects: the influence of evaporation and ventilation effects on the carbon and oxygen isotope composition of speleothems : a model approach - Deininger, Michael; Fohlmeister, Jens; Mangini, Augusto (Geochimica et cosmochimica acta, 2012)
In order to improve the understanding of variations of speleothem d18O and d13C values in the context of palaeoclimate research, it is important to quantify the isotope fractionation processes inﬂuencing the d18O and d13C values of stalagmites. Here we present an extended version of speleothem stable isotope model that accounts for evaporation and condensation eﬀects during precipitation of calcite. The ISOLUTION-model allows to calculate the eﬀect of evaporation on d18Ocalcite and d13Ccalcite values in dependence on relative humidity and wind velocity. Our results reveal that evaporation may have a signiﬁcant eﬀect on d18Ocalcite and d13Ccalcite due to the loss of H2O from the solution layer and the related increase of the Ca2+ concentration. This leads to higher precipitation rates and, consequently, larger isotope fractionation eﬀects. The eﬀect on speleothem d18Ocalcite and d13Ccalcite can be as high as changes caused by variations of temperature, drip interval, pCO2.drip and pCO2.cave. Furthermore, the change of pCO2.cave due to ventilation eﬀects, may also aﬀect speleothem d18Ocalcite and d13Ccalcite values because of the eﬀect of pCO2.cave on the equilibrium concentrations of the CO2-H2O-CaCO3-system and, thus, the calcite precipitation rate. The variability of other cave parameters (temperature, drip interval, pCO2.drip, pCO2.cave) can have a comparable eﬀect on d18Ocalcite and d13Ccalcite values depending on the magnitude of variability. We validated the ISOLUTION-model by modelling the d18Ocalcite values from a cave-analogue experiment and successfully reproduced the values for high temperatures.